2017
DOI: 10.1177/0010414017720702
|View full text |Cite
|
Sign up to set email alerts
|

The Legitimacy of Representation: How Descriptive, Formal, and Responsiveness Representation Affect the Acceptability of Political Decisions

Abstract: We examine how descriptive representation, formal representation, and responsiveness affect the legitimacy of political decisions: Who are the representatives, how are they selected, what is the outcome of the decisionmaking process, and to what extent do these three aspects matter for decision acceptance among the citizens? We examine this from the citizens' perspective, and ask whether decisions are perceived as more legitimate when they are made by groups that reflect society in certain characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 56 publications
1
59
0
3
Order By: Relevance
“…In particular, excluding women and ethnic minorities from political representation places these groups outside the political order, conveying their lack of full citizenship (Celis and Mazur ). Those concerned with legislative inclusion argue that decisions made about groups, but in the absence of group representatives capable of articulating group interests, are fundamentally unjust and may undermine the legitimacy of otherwise democratic institutions (Arnesen and Peters ; Mansbridge ).…”
Section: The Symbolic Effects Of Women In Politicsmentioning
confidence: 99%
“…In particular, excluding women and ethnic minorities from political representation places these groups outside the political order, conveying their lack of full citizenship (Celis and Mazur ). Those concerned with legislative inclusion argue that decisions made about groups, but in the absence of group representatives capable of articulating group interests, are fundamentally unjust and may undermine the legitimacy of otherwise democratic institutions (Arnesen and Peters ; Mansbridge ).…”
Section: The Symbolic Effects Of Women In Politicsmentioning
confidence: 99%
“…The key objective of this study was to investigate whether and to what extent ADM systems in policymaking influence public perceptions of EU input, throughput, and output legitimacy. Previous empirical studies have suggested that different decision-making arrangements (e.g., formal versus descriptive representation, direct voting versus deliberation) can differ significantly in terms of their perceived legitimacy (Esaiasson et al, 2012;Persson et al, 2013;Arnesen and Peters, 2018;Arnesen et al, 2019). However, as those studies did not specifically investigate the potential effects of ADM systems, the present study sought to distinguish between three different decision-making arrangements: (a) independent decision-making by EU politicians (HDM); (b) independent decision-making by ADM systems (ADM); and (c) HyDM by politicians, based on suggestions made by ADM systems.…”
Section: Hypothesesmentioning
confidence: 99%
“…By arguing that representation includes both a "making present" and an "acting for, " Pitkin (1967) suggests that it does not matter greatly who represents, as long as the ideas and preferences are represented. Representation in her view is not about the representative, for example, being a woman, but rather about the representative capturing relatively accurately whatever ideas and preferences the women constituent has that relate to policies (Arnesen and Peters 2018).…”
Section: Theoretical Framework Theory Of Political Representationmentioning
confidence: 99%